Kaderisasi dan Regenerasi dalam Lingkungan Keluarga: Studi Analisis Tematik terhadap Ayat-ayat Pendidikan - Komaruddin, Koko; Majdi, Ahmad Labib (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2021)
This paper wants to describe three issues that are the subject of discussion, namely the regeneration and regeneration of children in the family, the position of regeneration and regeneration of children in the family and educational values ​​in the process of regeneration and regeneration of children in the family. The regeneration of children referred to in this study has the meaning of efforts to prepare future generations or the next generation, namely children based on Islamic values ​​contained in the Koran. The method used in this study is a qualitative research method using a content analysis research design. This qualitative approach with content analysis method is then collaborated with the thematic interpretation method (maudhu'i). The results of the research in this paper are (1) the regeneration of children in the family environment according to the Koran is a planning system to educate, guide, and foster the regeneration of successors so that they are able to live properly and survive with the environment of their era; (2) the Koran has placed the position of regeneration as a necessity for mankind; (3) the educational values ​​for the regeneration of children in the family environment according to the Koran are the cultivation of mental attitudes to form a generation that is strong in faith, knowledge, and charity characterized by the cultivation of the values ​​of honesty, justice, trustworthiness, ta'awun, tasamuh, and istiqamah.